1991
DOI: 10.1093/ajcp/96.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Aminopeptidase IV Staining of Cytologic Preparations to Distinguish Benign from Malignant Thyroid Diseases

Abstract: Staining for dipeptidyl aminopeptidase IV (DAP IV [EC: 3.4.14.5]) activity was applied to aspiration biopsy specimens or imprint preparations of surgical biopsy specimens from thyroid tumors. Material was obtained from 55 patients with histologically proven thyroid diseases: 9 with papillary carcinoma, 5 with follicular carcinoma, 11 with follicular adenoma, 13 with adenomatous goiter, 8 with Hashimoto's thyroiditis, and 9 with other benign conditions. Most tumor cells, follicular lumina in cell clusters, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
2
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 16 publications
3
59
2
2
Order By: Relevance
“…Thyroid peroxidase ICC using MoAb 47 and DPP4-activation detection were the first malignancy markers reported to have a diagnostic significance on thyroid FNA smears (Aratake et al, 1992;De Micco et al, 1994a). In large series, TPO has been shown to have Se of 98% and Sp of 80% (Faroux et al, 1997;De Micco et al, 1998;Christensen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroid peroxidase ICC using MoAb 47 and DPP4-activation detection were the first malignancy markers reported to have a diagnostic significance on thyroid FNA smears (Aratake et al, 1992;De Micco et al, 1994a). In large series, TPO has been shown to have Se of 98% and Sp of 80% (Faroux et al, 1997;De Micco et al, 1998;Christensen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Staining was scored using a discontinuous 0 -12-point scale as described previously (Aratake et al, 1992). Positive controls were performed on smears from operated malignant nodules.…”
Section: Dpp4 Cytoenzymologymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of patient samples showed that CD26 is highly expressed on lung adenocarcinoma, thyroid carcinoma, and B-cell chronic lymphocytic leukemia (6)(7)(8). Meanwhile, CD26 is a marker of aggressive disease for selected subsets of T-cell non-Hodgkin's lymphomas/ leukemias.…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in T-cell biology through its physical and functional association with molecules involved in T-cell signal transduction processes (1)(2)(3)(4)(5)(6). Recent findings suggest that CD26/DPPIV has a role in the development of certain neoplasms, being overexpressed in certain aggressive T-cell malignancies (7,8), B-chronic lymphocytic leukemia (9), and thyroid carcinoma (10). On the other hand, loss or decreased surface expression of CD26/DPPIV is found in prostate cancer (11), colorectal carcinoma (12), and melanomas (13).…”
Section: Introductionmentioning
confidence: 99%